Avaliação da usabilidade do aplicativo móvel de uma instituição do ramo financeiro - Lottermann, Marcos (Universidade do Vale do Rio dos Sinos, 2018)
About 90.4% of the Brazilian population has access to banking services. This public is composed of a group of individuals with distinct characteristics. As such, their likes, interests and needs with regard to banking services vary greatly. Considering that mobile banking has consolidated the main banking channel used in the last years, the usability standards needed to be adapted for attending the mobile interfaces. Therefore, this paper deals with a case study in an area that is part of the IT Board at BAN Bank. In this context, this article shows the assessment of the usability of this institution's mobile application, based on ISO/IEC 25010 and ISO/IEC 25040 standards, using an assessment tool applied by an internal evaluation team. The research results show proposals for improvements and suggestions regarding the usability of the evaluated application.
Keywords: Serviços bancários; Mobile banking; Canal bancário; Banco BAN; ISO/IEC 25010 e 25040; Bank services; Mobile banking; Banking channel; Bank BAN; ISO / IEC 25010 and 25040